2018
DOI: 10.3390/polym10080907
|View full text |Cite
|
Sign up to set email alerts
|

Acylation of Lignin with Different Acylating Agents by Mechanical Activation-Assisted Solid Phase Synthesis: Preparation and Properties

Abstract: Acylated lignins with substituents consisting of different lengths of carbon chains were prepared by a mechanical activation-assisted solid phase synthesis (MASPS) technology with a customized stirring ball mill as a reactor. The structures and properties were analyzed by UV/Vis, FTIR, NMR, SEM, DSC, and TG. The results showed that the acylated lignins were successfully prepared with either non-cyclic or cyclic anhydrides as the acylating agents. Both aliphatic hydroxyl and phenolic hydroxyl groups of lignin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…It can be observed that lignin was covered by phthalic anhydride after modification. The surface of the modified lignin became rougher, mainly due to the removal of hydroxyl groups and elimination of intermolecular hydrogen bonding by esterification reactions [39]. This finding explained the reason why T g of composites prepared by PBS/ML and PBS/ML/KCF were lower than that of unmodified samples mentioned in the above section.…”
Section: Morphology Propertiesmentioning
confidence: 78%
“…It can be observed that lignin was covered by phthalic anhydride after modification. The surface of the modified lignin became rougher, mainly due to the removal of hydroxyl groups and elimination of intermolecular hydrogen bonding by esterification reactions [39]. This finding explained the reason why T g of composites prepared by PBS/ML and PBS/ML/KCF were lower than that of unmodified samples mentioned in the above section.…”
Section: Morphology Propertiesmentioning
confidence: 78%
“…CAB-MA prepared by the MA method was performed in a customized stirring ball mill [17]. Typically, 10.0 g of MCC mixed with butyric acid, acetic anhydride, and sulfuric acid catalyst (molar ratio of anhydroglucose unit (AGU) of MCC:butyric acid:acetic anhydride:sulfuric acid = 1:6:3:0.06) was poured into a 1200-mL jacketed stainless steel chamber containing 500 mL of zirconium oxide milling balls (Φ = 5 mm).…”
Section: Methodsmentioning
confidence: 99%
“…The hydroxyl groups of lignin react with acid, acid anhydride and acyl chloride in the presence of catalysts such as pyridine, 4-dimethylaminopyridine, 1-or N -methylimidazole, 2-methylimidazole, and imidazole, yielding esterified lignin. 152,153 Both the aliphatic and phenolic hydroxyl groups of lignin take part in the esterification reaction (Fig. 8).…”
Section: Functionalization Strategies For Ligninmentioning
confidence: 99%
“…Moreover, when the length of the carbon chain and the number of unsaturated bonds in the acyl groups increased, the reactivity of the esterifying agent decreased. 153 For catalysts, 4-dimethylamino pyridine, sodium acetate, and sulfuric acid all could enhance the esterification efficiency. 154 The esterification efficiency followed the order of 4-dimethylamino pyridine > sodium acetate > sulfuric acid.…”
Section: Functionalization Strategies For Ligninmentioning
confidence: 99%